Highly stretchable, robust, and conductive lab-synthesized PEDOT:PSS conductive polymer/hydroxyethyl cellulose films for on-skin health-monitoring devices - Han, Joo Won; Wibowo, Anky Fitrian; Park, Jihyun; Ha Kim, Jung; Prameswati, Ajeng; Entifar, Siti Aisyah Nurmaulia; Lee, Jonghee; Kim, Soyeon; Lim, Dong Chan; Moon, Myoung-Woon; Kim, Min-Seok; Kim, Yong Hyun (ELSEVIER, 2022)
Stretchable on-skin sensors provide multifunctional sensing in healthcare monitoring; however, it is challenging to develop cost-effective sensor materials with high stretchability, biocompatibility, mechanical robustness, and sensitivity. Stretchable conductive polymers have been extensively studied as a promising sensing material for strain sensors owing to their excellent stretchability, sensitivity, and mechanical durability. We demonstrate biocompatible on-skin sensors based on a highly conductive film consisting of a lab-synthesized polymer, poly (3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), and the biopolymer hydroxyethyl cellulose (HEC). Interface functionalization and post-treatment using 11-aminoundecanoic acid (11-AA) endow the PEDOT:PSS/HEC films with stronger bonds, high electrical conductivity, and mechanical robustness. The adhesion between PEDOT:PSS and HEC is greatly improved by the functionalization of the interface by 11-AA owing to the preferential formation of chemical bonds. Moreover, post-treatment with 11-AA enhances the electrical properties of the PEDOT:PSS film by removing the insulating PSS and changing the conformation of the PEDOT chains from benzoid to quinoid structure. Post-treatment reduces the sheet resistance of the interface-functionalized PEDOT:PSS film by 88.1% (from 4900 to 581 Omega/sq). The synergetic effects of interface modification and post-treatment using 11-AA also improve the mechanical characteristics of the PEDOT:PSS films, as demonstrated by tape attach-detach, cyclic stretching/releasing, and cyclic bending tests. Using the highly conductive and robust lab-synthesized PEDOT:PSS/HEC films, we develop highly biocompatible, stretchable, conformable on-skin sensors that can sensitively detect human motions, specifically, skin touch, finger bending, wrist bending, skin wrinkling, breathing, and walking, with excellent stretchability, excellent sensitivity, quick recovery, and conformality. We believe that the PEDOT:PSS/HEC films developed here have excellent potential for use in wearable on-skin devices that can detect various human motions owing to their outstanding performance and high stretchability, conductivity, robustness, and biocompatibility.